Analysis of noise sources in the acoustic field of a combine harvester's rotating thresher drum. Issue 1 (September 2020) - Stepanov, Valentin; Polushkin, Oleg; Kireev, Sergey; Korchagina, Marina
Abstract: The main goal of the current research is to analyze the acoustic field of the threshing unit of a combine harvester. This research implements a numerical simulation of gas flow based on the Navier-Stokes equations with discretization of equations by the finite volume method. The finite element mesh used in the idealized model allows one to adequately analyze noise sources up to a frequency of 2500 Hz based on the broadband noise source models of Curl and Proudman. In this paper, the analysis of the flow around the threshing unit at two rotation speeds of 500 rpm and 980 rpm was performed in order to point out elements contributing the most to the noise environment of a combine harvester in operation. As a result of the analysis, the spectra of maximum acoustic pressure and intensity were obtained. Based on this data, there were obtained design refinement areas and areas of increased technological control of a typical thresher drum for the practical implementation in the noise reduction strategies.